Monitoring calf circumference: changes during prolonged constrained sitting. Issue 4 (3rd April 2022) - Rigby, Laura; Frey, Mona; Alexander, Kara-lyn; De Carvalho, Diana
Abstract: Prolonged sitting has been associated with negative health effects; however, short-term time-varying exposure and response data is lacking. Twenty-two young and healthy participants were seated for 2  hours with the instruction to avoid the confounding effects of large leg movements while calf circumference, perceived discomfort, and lower limb muscle activity were collected. Calf circumference increased significantly (0.90 ± 0.32  cm) during sitting with no statistical differences between sexes. Perceived discomfort increased significantly over time in the low back and gluteal regions ( p  = 0.001–0.072, η p 2 =0.080–0.360). On average, it took 20.31 ± 10.87 minutes of walking for calf measures to return to pre-sitting baseline. These results suggest that sitting for 2 hours without activity breaks may not be advisable and that recovery may take longer than expected. The exposure/response data from this study may be helpful in the design of future studies, with a larger and more general population, aiming to better define recommended duration/activity ratios for sitting-focused occupations. Practitioner summary: Leg swelling is a concern in prolonged sitting. In this study of young, healthy participants, we found a 2 hour constrained sitting exposure (controlling for large leg movements) induced significant increases in calf circumference that took an average of 20.31 ± 10.87 min of walking to return to baseline. Abbreviations: FMD: flow-mediated dilation, GSC: gastrocnemius; TA: tibialis anterior; EMG: electromyography; VAS: visual analog scale; MVC: maximum voluntary contractions.